Food Losses and Waste, Beyond in Food Supply Chains: Retaining Optimum Nutrient Density - Eastham, Jane; Creedon, Annette (Current Perspectives in Agriculture and Food Science Vol. 8, 2024)
The present study explores the value of a holistic focus on the losses of nutrient density in food products where nutrients are lost within food systems. The paper is designed to open the debate around the loss of nutrient density and to discuss some of the existing research that might be drawn upon in a transdisciplinary approach. “Food systems” as a concept draws upon systems thinking and facilitates a transdisciplinary approach to address the complexity of delivering the Sustainable Development Goals in developed and developing food regimes. Previous research has assessed the causes of food loss and waste (FLW) and their effects on food accessibility and, consequently, nutrient availability using a food supply chain/systems approach. A key component of the sustainable agenda is making the most nutrients possible for the world's expanding population, and it is recognized that continuing to enhance food production is no longer the only way to achieve this. However, there is a drive for greater efficiency, not simply in the resources deployed, but in the utilization of the food produced. The study argues that FLW are not the only sources of nutrient loss within a supply chain and that there is a loss of nutrient density as the food progresses through the supply chain with the deterioration of nutrients in food within the food supply chain. It is argued here that in parallel to the management of loss and waste, there is a further need for a research agenda to explore the reality of the loss of nutrient density holistically as it passes from farm to fork, building on the existing scientific research at each tier within the supply chain. This paper extends the perspective of losses of nutrients beyond food loss and waste and calls for a transdisciplinary investigation of the losses of nutritional density throughout the supply chain in food that reaches the consumer. Bringing the food system into the nutritional discourse enables a greater understanding of the mutual interconnectivity and produces a more holistic approach that offers so much worth to our understanding of how the supply chain can retain and deliver optimal nutritional density for the consumer.